Beyond Ideology: China-Indonesia Engagement and the Making of the Guided Democracy, 1955-1959 - Kankan Xie (Journal of Indonesian Social Sciences and Humanities, 2016)
China’s engagement with Indonesia from 1955 to 1959 was neither ideologically oriented nor realpolitik, but somewhere in between. It happened not only because of the changing domestic political situations or completely subject to the shifting international environment, but was also closely associated with intrinsic social and historical issues that transcended geographical, ideological and ethnic boundaries within and across the two nation-states. To some extent, this effective engagement was not a result of Indonesia’s leaning towards the left, but a reason for it—not in the sense of direct political intervention, but through the pursuit of common identity and interest, which significantly shaped the making of Indonesia’s Guided Democracy.